´´Estrategias colaborativas para el proceso enseñanza aprendizaje en el área de estudios sociales en el cuarto año de educación básica en la escuela de educación General Básica ‘’Lic. Jaime Andrade Fabara´´ en el periodo 2018 – 2019’’ - Cachipuendo Cuzco, Cristian Sebastián (2021)
Nowadays, the education must be preceded by the use of strategies, methods and techniques that improve the teaching innovation and the integral student development. Schools must promote the application of methodological strategies and active techniques. So that, the teaching process learning is expressed in collaborative practices in the classroom. In this sense, the objective of this investigation consisted for proposing the Project- Based Learing strategy, strengthen the teaching-learning process through collaborative strategies in the area of social studies of the fourth grade, of the School of General Basic Education Lic. ´´Jaime Andrade Fabara´´, the investigation project was done from the qualitative approach, due to, it describes the reality educational fact; through techniques and instruments for the final result. The practical contributions of the investigation are educational and social because the field work was made in the teaching practice institutions of the Latacunga zone that proved the labor of the social groups investigated teams. Teachers, when executing the planning, execution and micro-curricular evaluation, they seek to transform the pedagogical meetings because they end up being a determining element in the stimulation of the student at the learning time. The handling of collaborative strategies devises a new way of innovating the education and this is summarized with the intervention of authorities, teachers, students and parents who see these initiatives and innovative processes of teaching and learning as part of the strengthening of the educational system.